1-Phenylethynylpyrene (PEPy) as a novel blue-emitting dye for qPCR assay. Issue 4 (7th January 2016) - Aparin, Ilya O.; Farzan, Valentina M.; Veselova, Olga A.; Chistov, Alexey A.; Podkolzin, Alexander T.; Ustinov, Alexey V.; Shipulin, German A.; Formanovsky, Andrey A.; Korshun, Vladimir A.; Zatsepin, Timofei S.
Abstract : We demonstrated that 1-phenylethynylpyrene (PEPy) is a superior substitute for AMCA and Alexa-350 as a short wavelength fluorescent dye for end-point PCR and quantitative PCR. This study broadens the panel of fluorescent dyes suitable for the use in Taqman probes. Abstract : An alkyl azide derivative of 1-phenylethynylpyrene (PEPy) dye was prepared and used in the functionalization of oligonucleotides via click chemistry. Spectral and photo-physical properties of the PEPy-modified oligonucleotides as a single strand, and in perfect or mismatched duplexes, have been studied. A series of PEPy–Dabcyl fluorogenic TaqMan probes were synthesized and tested in qPCR. PEPy proved to be a superior substitute for AMCA as a short wavelength fluorescent dye for qPCR probes. PEPy probes were shown to significantly reduce Cq (a fractional PCR cycle used for quantification) vs. AMCA labeled probes, thus improving on the reliability of detection. Moreover, a larger increase of fluorescence during amplification was observed in the case of PEPy probes that makes this dye very suitable for an end-point PCR technique. This study broadens the panel of fluorescent dyes suitable for the use in probes for quantitative real-time PCR.